1995
DOI: 10.1002/1097-0142(19950515)75:10<2507::aid-cncr2820751017>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of breast cancer screening by age. New results swedish two-county trial

Abstract: Background. Several studies have found a smaller effect of breast cancer screening on breast cancer mortality in women aged younger than 50 years compared with older women. Various possible reasons have been suggested for this, but none firmly is established. Methods. The Swedish Two‐County Study is a randomized trial of breast cancer screening of women aged 40‐74 years, comprising with 133,065 women with a 13‐year follow‐up of 2467 cancers. The Breast Cancer Detection Demonstration Project (BCDDP) is a nonran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
237
0
13

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(265 citation statements)
references
References 20 publications
11
237
0
13
Order By: Relevance
“…A number of other potential problems with the use of surrogate end points have been discussed by Morrison (1991), such as variation of prognostic factors within measurement categories, most of which would tend to lead to an underestimate of the effect of screening. The analysis of the Swedish Two County Study found that the predicted effect on mortality in the age group 40 -49 years was conservative compared with that observed (Tabar et al, 1995b). The authors hypothesised that this might be attributable to an observed excess of cancers in the intervention arm, possibly due to over diagnosis in this age group, or the existence of a subgroup of women with a long sojourn time.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A number of other potential problems with the use of surrogate end points have been discussed by Morrison (1991), such as variation of prognostic factors within measurement categories, most of which would tend to lead to an underestimate of the effect of screening. The analysis of the Swedish Two County Study found that the predicted effect on mortality in the age group 40 -49 years was conservative compared with that observed (Tabar et al, 1995b). The authors hypothesised that this might be attributable to an observed excess of cancers in the intervention arm, possibly due to over diagnosis in this age group, or the existence of a subgroup of women with a long sojourn time.…”
Section: Discussionmentioning
confidence: 95%
“…The Swedish Two-County Studies Survival index uses information on size, lymph node status, grade and histological type, and has been developed using data from the randomised trial (Tabar et al, 1995b). The relative hazards of different factors, including lymph node status, have previously been validated against observed mortality reduction in the trial in different age-groups including women aged 40 -49 (Tabar et al, 1995a).…”
Section: Pathology Datamentioning
confidence: 99%
“…(1) Prognostic model: A Cox proportional hazards model was developed to predict breast cancer-specific survival based on methods published by Tabar et al (1995) and Haybittle et al (1982), using the 'prognostic sample' described above. Age,tumour size (p9,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]50 þ mm,unknown), nodal status (negative, positive, unknown) and histologic grade (well, moderately, or poorly differentiated and unknown) were examined as potential prognostic factors.…”
Section: Analytic Schema/statistical Methodsmentioning
confidence: 99%
“…Clinical mammography worked significantly better in women above the age of 70 than in women below the age of 50, which is to be expected because of the more favourable differences in contrast on mammography between cancer and the surrounding fatty tissue predominantly seen in elderly age groups. 38 As organized mammography screening was offered in only 2 out of 15 regions in Denmark in 2000 to women aged 50-69, and as the spectrum of accepted reasons for referral to clinical mammography was relatively broad, these examinations may to some extent also have been used for opportunistic screening. We used annual utilisation rate in the region as an indicator of the extent to which the examinations of truly symptomatic women had been mixed with Values in parentheses represent 95% confidence interval.…”
Section: Discussionmentioning
confidence: 99%